Rancang Bangun Mesin Ektrusi Pembuat Filamen dengan Sistem Screw Conveyor - Rusdi Nur; Nursyahbani P Parahdiba; Ikhlas Abdullah; Dimas F Roji; Sitti Sahriana; Ilyas Mansur (Politeknik Negeri Ujung Pandang, 2022)
Plastic extrusion machine is a tool to carry out the process of extrusion or formation by utilizing plastic blockage by using high temperatures for the process of melting and reshaping with mold into a certain form, where the drive used in the extrusion machine is a power thread formed in such a way as to be able to conduct or move the material. Extrusion machine made with the principle of horizontal shape and use screw conveyor as a material drive in the extrusion process. Extrusion Machine uses HDPE pellets as a test material to print filaments with a attached specification of 31.81 rpm of speed and 915 watt of element band heater power. The process of designing an extrusion machine with the screw conveyor was using standard flight or standard blade, on the grounds that the screw or thread only serves to move the material to the end of the nozzle. The screw conveyor size is 500 mm long, screw diameter is 50 mm and the distance between pitches is 25 mm followed by the dimensions of the machine is 800 x 400 x 600 mm. The test results were conducted using HDPE polyethylene pellet material with variable temperature variations consisting of 5 types of temperature, namely, 120 ° C, 110 ° C, 110 ° C, 95 ° C and 90 ° C, form the five variables above we conducted trials on each temperature. Then we got it and we concluded that the experiment using the temperature variable of 100 ° C has the most optimum output results, where the temperature of 120 ° C and 110 ° C has a liquid output result then the temperature of 90 ° C and 95 ° C has a condition where the material dries too quickly and make the nozzle clogged.